The Role of Natural Schools in Cultivating 4C Skills to Face the Challenges of the 21st Century - Tiok Wijanarko; Singgih Ginanjar; Lidya Febrianti; Athirah Dewi; Shinta Dewi Novitasari (Jurnal Penelitian Pendidikan IPA, 2024)
The research uses a qualitative type with descriptive analysis methods: data collection techniques using interviews, observation, and documentation. The research results show that the cultivation of 4C skills is carried out through learning and school programs. Learning at nature schools uses a learning method: Learning with Nature (BBA). Through BBA learning, students are invited to identify problems and conclude problems related to learning. Students are also invited to form groups independently, divide tasks, work creatively, and communicate group work results. Instilling scientific literacy and 4C skills is also done through programs outside of learning. The planned programs include super camps, educational visits/trips, trading agricultural products, and Alek Minangkabau. The results of this research are the basis for conducting studies on instilling and improving 4C skills in elementary schools